2021
DOI: 10.1155/2021/6219678
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors of Delirium in the Intensive Care Unit: A Prospective Cohort

Abstract: Purpose. The purpose of this study was to determine the incidence, risk factors, and impact of delirium on outcomes in ICU patients. In addition, the scoring systems were measured consecutively to characterize how these scores changed with time in patients with and without delirium. Material and Methods. A prospective cohort study enrolling 400 consecutive patients admitted to the ICU between 2018 and 2019 due to trauma or surgery. Patients were followed up for the development of delirium over ICU days using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
(21 reference statements)
3
7
0
Order By: Relevance
“…The incidence of delirium in our study was 31.8% with the median onset of delirium being 3 (IQR = 2) days after admission. Although the incidence of delirium in our study was similar to previous studies reporting an incidence of 27–32% in ICU patients (Jayaswal et al, 2019; Ouimet et al, 2007; Rahimi‐Bashar et al, 2021), on the contrary, it was much lower than studies reported with an incidence of up to 80% (Ely, Gautam, et al, 2001; Ely, Margolin, et al, 2001; Girard et al, 2010; Shehabi et al, 2010). The reason for these differences can be explained by the characteristics or settings of the studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…The incidence of delirium in our study was 31.8% with the median onset of delirium being 3 (IQR = 2) days after admission. Although the incidence of delirium in our study was similar to previous studies reporting an incidence of 27–32% in ICU patients (Jayaswal et al, 2019; Ouimet et al, 2007; Rahimi‐Bashar et al, 2021), on the contrary, it was much lower than studies reported with an incidence of up to 80% (Ely, Gautam, et al, 2001; Ely, Margolin, et al, 2001; Girard et al, 2010; Shehabi et al, 2010). The reason for these differences can be explained by the characteristics or settings of the studies (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…APACHE II and SOFA scores represent illness severity and organ dysfunction, respectively. The APACHE II and SOFA scores in our study were 14.2 ± 5.7 and 8.4 ± 5.4, respectively, indicating severe illness in our patients and explaining the high incidence of delirium, which is supported by other studies (Rahimi-Bashar et al, 2021). We found that delirium was a frequent complication in older ICU patients, which was similar to previous studies (Tafelmeier et al, 2019;Eertmans et al, 2020).…”
Section: Figuresupporting
confidence: 91%
“…There was no significant difference in the incidence of delirium between patients with COVID-19 and those without COVID-19. Based on this, other factors were more likely involved in the development of delirium among patients admitted to the ICU.The GEE revealed that the CFS and SOFA scores upon ICU admission were significant indicators for the development of delirium, which is in line with the results of previous studies[6] [20]. Frail patients were reportedly more susceptible to stress, which results in inflammation, and they might be more likely to become delirious[18] [21].…”
supporting
confidence: 87%